Social Welfare Policy and Cross-Sectoral Participation: For Resilience Overcoming Stunting in Indonesia - Rusliadi Rusliadi; Asri Nur Aina (Government & Resilience, 2024)
Efforts to reduce poverty must have an impact that can reach the various problems caused by poverty. This research aims to analyze social policies related to poverty alleviation and cross-sectoral participation in overcoming stunting problems that occur in Indonesia. This research uses a qualitative-exploratory research method to examine the Government's Social Policy in overcoming poverty and its impact on stunting which involves cross-sector participation in its implementation. Then the data is collected from interviews, field observations, and applicable literature, then to analyze the results using Nvivo 12 Pro. The location of this research uses a regional case study in Indonesia, namely the Bantaeng Regency area. The results of this study show that the contribution of government social policies in overcoming poverty has a very positive impact on reducing the number of stunting that occurs in Bantaeng Regency. Several programs issued by the government focus on increasing consumption and fulfilling community nutrition by assisting with food. Then cross-sectoral participation in handling stunting in Bantaeng Regency has also been going well, because it not only involves the local government but also involves the military. However, this study found that there was a lack of involvement of the private sector in efforts to help the government deal with the problem of stunting. So that this is a weakness in handling stunting, therefore in handling stunting based on government programs there needs to be a binding regulation to involve the private sector.